Terre Napoléon A History of French Explorations and Projects in Australia - Scott, Ernest (Cambridge library collection. History of Oceania, 1910)
Ernest Scott (1867–1939) emigrated to Australia in 1892, settling in Melbourne where he worked as a journalist. In 1913 he was appointed Professor of History at the University of Melbourne. This volume, first published in 1910, discusses the aims and outcome of the survey of the south Australian coast performed by Nicholas Baudin's French expedition between 1800 and 1804, and established Scott's reputation as a historian. Scott traces the path of Baudin's expedition along the then unexplored south coast of Australia, estimating the amount of original surveying performed by the expedition to address the accusation that the French expedition plagiarised British surveys of the same coastline. Scott also discusses the origins of the expedition to investigate possible political motivations behind the survey. This detailed and meticulously researched volume presents a valuable revised view of Baudin's expedition